Policy factors explaining the failure of delegated management in water supply: evidence from Ghana. Issue 1 (2nd January 2019) - Mvulirwenande, Silas; Wehn, Uta; Alaerts, Guy
ABSTRACT: In the 1990s, delegated management emerged as a promising public policy approach for improving the performance of the water supply sector in many developing countries. In many cases, however, the obligations of delegated management contracts reportedly have not been met, often leading to early termination or non-renewal. Drawing on theories in policy analysis and knowledge management, this article analyzes the management contract signed between Ghana Water Company and Aqua Vitens Rand to identify the policy-related factors underlying the failure of delegated management in water supply. Practical implications are discussed for more successful implementation of delegated management.